Permeation-enhancing effects and mechanisms of O-acylterpineol on isosorbide dinitrate: mechanistic insights based on ATR-FTIR spectroscopy, molecular modeling, and CLSM images - Yan Li; Chunyan Wang; Jian Wang; Tianzhe Chu; Linlin Zhao; Ligang Zhao (Taylor & Francis Group, 2019)
The present study aimed to evaluate the penetration activity of O-acylterpineol derivatives both in vitro and in vivo, and to investigate the enhancing mechanism of O-acylterpineol derivatives which were synthesized by α-terpineol and fatty acid. The promoting activities on the isosorbide dinitrate patch were tested across full thickness rabbit skin both in vitro and in vivo. In order to elucidate the permeation mechanism, attenuated total reflection Fourier transform infrared spectroscopy, molecular modeling, and confocal laser scanning microscopy were introduced to investigate the regulation of enhancers in the skin permeability and biophysical properties. With in vitro cytotoxicity test and in vivo erythema model, the skin irritation of enhancers was also evaluated. Permeation studies showed 2-(4-methylcyclohex-3-en-l-yl) propan-2-yl tetradecanoate produced the obvious enhancement activity for ISDN both in vitro and in vivo from patches. These results were supported by ATR-FTIR, molecular modeling, and CLSM studies which revealed that O-acylterpineol could decrease the order of the alkyl chains in the skin lipids. Additionally, it was found that TER-C14 produced a relatively low skin irritation, compared with the TER which was assumed to be a safe compound. The present research suggested that some newly designed acylterpineol derivatives are shown to be suitable permeation enhancers for transdermal drug delivery, and the chain length of C14 seem to be safe and more favorable for the penetration of ISDN from DIA patches.